The moderating role of technological innovation on ownership structure, financing decisions and environmental accounting disclosure - Ummar Faruk Saeed; Rabiatu Kamil; Ishmael Wiredu (Cogent Business & Management, 2024)
This study investigates the effect of ownership structure (OS) and financing decisions (FD) on environmental accounting disclosure (EAD), considering the moderating role of technological innovation (TI). Despite the growing emphasis on corporate sustainability, there is limited understanding of how different ownership structures and financing choices influence EAD, particularly when moderated by TI. Drawing insights from agency and stakeholder theories, this research aims to fill this gap by analyzing manufacturing companies in the MENA region from 2001 to 2022. Using Dynamic Common Correlated Effects (DCCE) estimation, we examine the empirical relationships among these variables. To address endogeneity issues, the study employed GMM modeling. Our findings reveal that concentrated ownership and state ownership significantly promote EAD, while managerial ownership has a negative impact. Additionally, firms relying on equity financing tend to exhibit higher EAD, whereas those relying on debt financing show lower EAD levels. Notably, technological innovation positively moderates the relationship between ownership structure and EAD. The findings underscore the importance of promoting equity financing, concentrated ownership, and state ownership to enhance EAD in the MENA region. Furthermore, the study emphasizes the need for adopting innovative practices to improve environmental disclosure standards and support sustainable business practices.
Keywords: 650; Environmental disclosure; financing decisions; MENA nations ownership structure; technological innovation